2018
DOI: 10.1002/hep.29496
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments of c‐Met as a therapeutic target in hepatocellular carcinoma

Abstract: Aberrant c‐Met activity has been implicated in the development of hepatocellular carcinoma (HCC), suggesting that c‐Met inhibition may have therapeutic potential. However, clinical trials of nonselective kinase inhibitors with c‐Met activity (tivantinib, cabozantinib, foretinib, and golvatinib) in patients with HCC have failed so far to demonstrate significant efficacy. This lack of observed efficacy is likely due to several factors, including trial design, lack of patient selection according to tumor c‐Met st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
166
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(192 citation statements)
references
References 92 publications
1
166
0
Order By: Relevance
“…c‐Met, a famous oncogene, has been demonstrated to promote the HCC progression, and been developed as a therapeutic target in HCC . We found that HN1 expression was positively correlated with c‐Met expression in these four HCC cell line.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…c‐Met, a famous oncogene, has been demonstrated to promote the HCC progression, and been developed as a therapeutic target in HCC . We found that HN1 expression was positively correlated with c‐Met expression in these four HCC cell line.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, decreased expression of c‐Met was also detected in the HN1‐depleted melanoma cells . c‐Met, the receptor tyrosine kinase (RTK) of HGF, has been demonstrated to promote the HCC progression . The expression of c‐Met was closely associated with early recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…We identified around 22% of potentially targetable genetic alterations in advanced HCC, mainly including alterations of AKT/mTOR and the MET pathway or ligand amplification, such as VEGFA and FGF19 . The MET pathway has been considered an appealing target in patients with advanced HCC . However, a recent phase 3 randomized controlled trial comparing tivantinib, initially considered a MET inhibitor, versus placebo in advanced HCC with MET overexpression at immunohistochemistry failed to improve overall survival .…”
Section: Discussionmentioning
confidence: 99%
“…The MET pathway has been considered an appealing target in patients with advanced HCC. (22) However, a recent phase 3 randomized controlled trial comparing tivantinib, initially considered a MET inhibitor, versus placebo in advanced HCC with MET overexpression at immunohistochemistry failed to improve overall survival. (23) This negative result could be explained by the fact that tivantinib was ultimately not a MET inhibitor and that MET overexpression at immunohistochemistry was not a reliable surrogate marker of oncogene addiction to the MET pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of c‐Met is associated with vascular invasion, tumor growth, and poor prognosis in cancer patients . Subsequently, targeting c‐Met has become a major strategy for novel cancer treatment, and numerous clinical trials are currently underway trialing the effect of monoclonal antibodies and small molecule inhibitors of c‐Met (reviewed by Bouattour et al …”
Section: Introductionmentioning
confidence: 99%